The role of knowledge, attitude, gender, and school grades in preventing drugs use: findings on students' intentions to participate in peer education program - Ira Nurmala; Muthmainnah Muthmainnah; Iswari Hariastuti; Yuli Puspita Devi; Nurvita Ruwandasari (SAGE Publishing, 2021)
Background: Student groups are prone to drug abuse. The prevalence of drugs in the past year among high school students in Surabaya, Indonesia occupies the highest provincial capital (9.4%). The purpose of this study analyzed the relationship between knowledge about drugs, attitudes about peer education, gender, class, and students' intention to participate in peer education programs in HEY (Health Educator for Youth) activities. Design and Methods: A cross-sectional study was conducted with student participants (12-18 years) in six high schools in Surabaya, Indonesia (n=167). This study used an online survey to assess knowledge of drugs and students' attitudes about HEY peer education activities. Results: More than half of the students have insufficient knowledge about drugs and have negative attitudes about peer education in HEY activities. This study also showed that students' intention to participate in peer education was not influenced by the level of knowledge, student attitudes, and gender. The results of statistical tests showed that there was a relationship between class and student participation in peer education activities. This showed that the student's factor regarding participation in peer education was a class category where the lower class is more motivated to participate. Conclusion: Most students have less knowledge about drugs and a negative attitude about peer education. However, the intention to participate in peer education activities is more thus it is necessary to improve the quality of peer educators through activities that are performed regularly by various relevant stakeholders.